Counseling on Simple Bookkeeping for Residents of Simak Boarding House, Rowolaku Village, Kajen, Pekalongan - Sulis Setiyaningrum; Lia Khoirina; Nur Zalfa Rifqo Nabila; Hendri Hermawan Adinugraha; Ade Gunawan; Matteson Niva (Yayasan Adra Karima Hubbi, 2023)
Background. Accounting is a systematic process for processing transactions into useful financial information for its users. Financial bookkeeping can be regarded as an information center in a business. In the bookkeeping, you can see the financial condition of both income and expenses. You can also develop a strategy according to the budget you have. Purpose. This activity aims to help boarding school residents to make simple financial reports and provide an overview of basic accounting introductions. Method. Activities using counseling methods and direct presentations to boarding house residents are seen by providing direct examples of financial report explanations. Implementation of counseling is done by explaining the theories needed and continuing with practice. After counseling was held, he opened a consulting clinic to help with the bookkeeping problem. The data source used in this service is primary data. The data collection technique used is by finding out the desired information about the problems faced by boarding house residents through counseling. Data analysis techniques are carried out by searching and compiling data, describing data, compiling data and selecting data to study and making conclusions. Results. The implementation of this Community Service can be well received by the residents of the boarding house without any rejection, and the residents of the boarding house express their gratitude for this activity. This indicates good acceptance of this service activity as a form of concern. Community service activities for boarding house residents and students who focus on simple accounting training for boarding children. Conclusion. The conclusion from this counseling is that the boarding house residents know about financial management to minimize expenses.